2019
DOI: 10.4149/bll_2019_021
|View full text |Cite
|
Sign up to set email alerts
|

The role of selenium in bevacizumab induced cardiotoxicity

Abstract: OBJECTIVE: We investigated the role of selenium in bevacizumab induced cardiotoxicity and involvement of transient receptor potential vanilloid 1 (TRPV1) channels in cardiomyocytes. MATERIALS AND METHODS: All cells (Human cardiomyocyte cell line) were cultured at 37 °C. We divided the cells into seven groups as control, bevacizumab, bevacizumab + capsazepin, bevacizumab + selenium, bevacizumab + selenium + capsazepin, selenium and selenium + capsazepin groups. Cells in the groups were stimulated with capsaicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Lung cancer or thoracic cancers are frequently managed with immunotherapy, radiation, chemotherapy as monotherapy, or radiation combined with chemotherapeutic agents, such as platinum (cisplatin and carboplatin), microtubule inhibitors taxanes (docetaxel and paclitaxel), blood vessel formation inhibitors (bevacizumab), epidermal growth factor inhibitors (erlotinib and necitumumab), and immunotherapies [ 23 ] (nivolumab, pembrolizumab, atezolizumab, and ipilimumab). Cancer therapeutics cause cardiopulmonary toxicities including hypertension and myocardial ischemia [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], and this is accepted by the American Cancer Society and American Heart Association. According to the US National Cancer Institute (NCI) and based on our previous knowledge, chemotherapy or immunotherapy promote toxicity/inflammation in non-target organs and these inflammations invite migration of neutrophils, macrophages, and cytotoxic lymphocytes to injured and non-injured sites [ 6 ].…”
Section: Cancer Therapy-induced Inflammation and Cardiopulmonary Fibrosismentioning
confidence: 99%
“…Lung cancer or thoracic cancers are frequently managed with immunotherapy, radiation, chemotherapy as monotherapy, or radiation combined with chemotherapeutic agents, such as platinum (cisplatin and carboplatin), microtubule inhibitors taxanes (docetaxel and paclitaxel), blood vessel formation inhibitors (bevacizumab), epidermal growth factor inhibitors (erlotinib and necitumumab), and immunotherapies [ 23 ] (nivolumab, pembrolizumab, atezolizumab, and ipilimumab). Cancer therapeutics cause cardiopulmonary toxicities including hypertension and myocardial ischemia [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], and this is accepted by the American Cancer Society and American Heart Association. According to the US National Cancer Institute (NCI) and based on our previous knowledge, chemotherapy or immunotherapy promote toxicity/inflammation in non-target organs and these inflammations invite migration of neutrophils, macrophages, and cytotoxic lymphocytes to injured and non-injured sites [ 6 ].…”
Section: Cancer Therapy-induced Inflammation and Cardiopulmonary Fibrosismentioning
confidence: 99%
“…In addition, high serum troponin I (TP I) and creatine kinase MB (CK‐MB) levels were found in BVZ‐treated rats 6 . Moreover, studies have shown that human cardiomyocytes treated with BVZ exhibited increased cytosolic calcium, apoptosis, and reactive oxygen species (ROS) production 7 . However, the intracellular molecular mechanisms underlying BVZ‐associated cardiotoxicity have yet to be fully understood.…”
Section: Introductionmentioning
confidence: 99%
“… 6 Moreover, studies have shown that human cardiomyocytes treated with BVZ exhibited increased cytosolic calcium, apoptosis, and reactive oxygen species (ROS) production. 7 However, the intracellular molecular mechanisms underlying BVZ‐associated cardiotoxicity have yet to be fully understood. A previous study reported that VEGFA was involved in BVZ‐induced cardiomyocyte toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperglycemia and hyperlipidemia lead to mitochondria dysfunction which causes cellular energy depletion and reactive oxygen species (ROS) generation and finally results in hepatocellular apoptosis and death (Gouaref et al 2017;Tilg et al 2017). Previous studies demonstrated that the transient receptor potential receptor vanilloid 1 (TRPV1) is a mechanosensitive ion channel that has been shown to regulate the energy expenditure and cholesterol metabolism in hepatocytes (Wang et al 2013;Harb et al 2019), while activation of TRPV1 has been identified to protect against stresses induced oxidative toxicity in various cells such as neuronal cells (Ataizi and Ertilav 2020), cardiomyocytes (Oncel and Ovey 2019), human umbilical artery smooth muscle cells (Schwartz et al 2018) and bone marrow-derived macrophages (Yan et al 2019). Therefore, we infer that TRPV1 could modulate redox signals to prevent high glucose-and high fatty-acid-intake-induced liver injury.…”
Section: Introductionmentioning
confidence: 99%